Digital technology, green innovation, and the carbon performance of manufacturing enterprises - Li, Jinke; Ji, Luyue; Zhang, Shuang; Zhu, Yanpeng (Frontiers in Environmental Science, 2024)
Accompanied by the continuous promotion of digitalization development and the global trend towards a low-carbon economy, whether enterprises can enhance their carbon performance with the assistance of digital technology has aroused widespread attention from both academia and industry. In order to explore whether digital technology can achieve the improvement of carbon performance of manufacturing enterprises and its implementation path, this article, based on the resource orchestration theory and the signaling theory, uses the data of China's A-share manufacturing enterprises from 2012 to 2021 to empirically investigate the relationship between digital technology and carbon performance of manufacturing firms, and further explore the mediating conduction path and boundary influencing factors between the two. Findings demonstrate that digital technology is capable of improving carbon performance, green innovation (including green technology innovation, green collaborative innovation) has partially mediating effects, and there is a catalytic role for environmental information disclosure in utilizing digital technology to enhance carbon performance. Building on the discoveries, we find that the impacts of digital technology, green innovation, and environmental information disclosure on carbon performance vary due to differences in industry nature and enterprise strategic aggressiveness. Specifically, the role of digital technology on carbon performance looks somewhat more pronounced among firms in the high-tech industry and those employing defensive and analytical strategies. Additionally, the effects generated by green innovation and environmental information are more pronounced in the high-tech industry and among enterprises that adopt analytical strategies. The study reveals the inherent mechanism of digital technology in enhancing carbon performance of manufacturing enterprises, which provides empirical evidence for the development of digital technology and the improvement of carbon performance in manufacturing enterprises, helping to promote low-carbon economic transformation.